Usual dietary intake and change in DNA methylation over years: EWAS in KORA FF4 and KORA fit - Hellbach, Fabian; Freuer, Dennis; Meisinger, Christa; Peters, Annette; Winkelmann, Juliane; Costeira, Ricardo; Hauner, Hans; Baumeister, Sebastian-Edgar; Bell, Jordana T.; Waldenberger, Melanie; Linseisen, Jakob (Frontiers in Nutrition, 2024)
Changes in DNA methylation can increase or suppress the expression of health-relevant genes. We investigated for the first time the relationship between habitual food consumption and change in DNA methylation. The German KORA FF4 and KORA Fit studies were used to study the change in methylation over a median follow-up of 4 years. Only subjects participating in both surveys and with available dietary and methylation data were included in the analysis (n = 465). DNA methylation was measured using the Infinium MethylationEPIC BeadChip (Illumina), resulting in 735,527 shared CpGs across both studies. Generalized estimating equation models with an interaction term of exposure and timepoint were used to analyze the association of 34 food groups, folic acid and two dietary patterns with change in DNA methylation over time. The results were corrected for genomic inflation. Significant interaction terms indicate different effects between both time points. We observed only a few significant associations between food intake and change in DNA methylation, except for cream and spirit consumption. The annotated genes include CLN3, PROM1, DLEU7, TLL2 and UGT1A10. We identified weak associations between food consumption and DNA methylation change. The differential results for cream and spirits, both consumed in low quantities, require replication in independent studies.